Memahami Faktor Pembentuk Niat Pembelian Online di Indonesia: Eksistensi Sosial dalam e-Commerce, Sinyal Afiliasi Politik, Persepsi Kewajaran Harga, dan Kepercayaan - Harnaji, Bimo; Andika, Andika; Putri, Wika Harisa (Universitas Batanghari, 2024)
In the context of Industry 4.0, widespread internet penetration has significantly changed social and political dynamics and consumption behavior. This study analyzes the influence of social presence in e-commerce, perceived price fairness, and consumer trust on online purchase intentions in Indonesia, including these variables' direct and indirect impacts. This study also explores the role of political affiliation in the context of online image management by public figures, which is relevant for business continuity in Indonesia. The study adopted a quantitative approach, surveying 153 respondents in Indonesia. Data was collected and analyzed using Descriptive Statistical Analysis and Structural Equation Modeling (SEM) to validate the proposed hypotheses. The findings show that social presence in e-commerce partially influences perceived price fairness and trust. Similarly, perceived price fairness and trust have a partially significant impact on purchase intentions in online marketplaces. However, political affiliation signals have no significant influence on online purchase intentions. This research provides new insights into the dynamics of online purchasing in Indonesia, particularly concerning social and political factors. The findings are essential for e-commerce businesses to develop more effective marketing strategies, considering social aspects and perceived price fairness. In addition, this study suggests the importance of separating political image from online business activities for public figures and politicians to avoid negative impacts on consumer perceptions. Academics and practitioners can use these findings as a basis for further research examining the impact of socio-political variables on online consumer behavior.